Klaster jako narzędzie kreowania regionalnych innowacji w turystyce - Januszewska, Małgorzata; Nawrocka, Elżbieta (Cluster as a Tool for Creating Regional Innovation in Tourism, 2008)
For a few years cluster systems have been a preferred form by the European Union of introducing innovation in different economic domains, including the domain of tourism. In this process the role of regions is emphasized as the one of areas for creating new projects. The article presents some research questions referring to theoretical sources of innovation, the changeability of concepts related to them, the role of clusters in the construction of innovative areas for the reception of tourist traffic and their practical illustration. On the basis of the conducted research there are presented chances and threats for the development of cluster initiatives in Polish tourism. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 29, s. 95-105